HUBUNGAN SIKAP, MOTIVASI BELAJAR DAN PEMANFAATAN MEDIA PEMBELAJARAN DENGAN PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL EKONOMI - Jacinta Karmila; Herpratiwi Herpratiwi; Adelina Hasyim (Faculty of Teacher Training and Education, University of Lampung, 2013)
The research has the aims to describe the correlation of attitude, motivation and media for learning toward students’ achievement in Economics learning: (1) the correlation of attitude and students’ achievement in learning Economics; (2) the correlation of motivation with students’ achievement in learning Economics; (3) the correlation of media for learning and students’ achievement in learning Economics; (4) the correlation of attitude and motivation with students’ achievement in learning Economics. Research method used in the research is correlation technique. The number of population is 162 students with 117 students as samples. Research data had taken by giving questionaires and tests to the students. Some techniques of data analysis used in the research are linear correlation and partial correlation. The conclusions of the research are: (1) attitude has a correlation with students’ achievement in learning Economics with linear correlation coefficient is 0.328 and partial correlation coefficient is 0.243; (2) motivation has a correlation with students’ achievement in learning Economics with linear correlation coefficient is 0.316 and partial correlation coefficient is 0.246; (3) media for learning has a correlation with students’ achievement in learning Economics with linear correlation coefficient is 0.303 and partial correlation coefficient is 0.226; (4) attitude and motivation have a correlation with students’ achievement in learning Economics with linear correlation coefficient is 0.324 and partial correlation coefficient is 0.238.Keywords: attitudes, motivation, media for learning